EFFECTS OF THE DEPRESSION SELF-DESTRUCTIVE INSTALLATION IN RELATION: GENETICS, METABOLISM AND RISKS IN THE ORGANIC CEREBRAL STRUCTURE - Montero Doig, Ana (2020)
The purpose of this article is to show the effects of the Self-Destructive Instinct due to depression in relation to the levels: genetic, metabolic and risks of the cerebral organic structure; also, the methodology is quantitative with correlational experimental design. Likewise, it will be commented on convergent and divergent neural networks, their connections, the role of impressions/associations in the chain of instinctive selfdestructive sensoromotor data of harmful behaviors of food consumption, appetite and behaviors of affective indicators, and other cognitive compulsions, which leave traces of significant mental and physical health risks in all critical periods of animal and human psychological development. The samples are  composed of 40 lower mammalian subjects; albino rats (N° 20) and human superiors (N° 20), the sensorial-perceptive role will be investigated and observed; carried with an attention to the alimentary behavior,consumption, affective indicators of the self-destruction and cognitive compulsions in front of the mysteries of the force of the life and its changes.